Interaction Effect of Dual N-back Working Memory Training and Anxiety Levels on L2 Writing Performance - Khelalfa, Nawal; Merrouche, Sarah (Journal of Human Sciences, 2019)
Burgeoning interest in the role of working memory (WM) in most cognitive endeavors has led to an increase in WM training programs. Within the field second language writing, however, WM improvement interventions are scarce, and even scarcer is research into how other variables interactwith WM in their effect on performance. Hence, this study examines how anxiety, often believed to be an impediment for both WM and writing, moderates the effect of WM training on writing. Learners’ (N=80) writing performance was assessed before and after Dual N-back training. Anxiety levels were examined for any interaction with the intervention. Results from ANCOVA, Pearson’s correlation, and Two-Way ANOVA have revealed that writing anxiety is significantly correlated with writing performance and that the treatment group outperformed the control group even after controlling for both initial performance and anxiety levels. The findings indicate that there is a significant anxiety-treatment interaction effect on writing performance